Alkali fusion of bauxite refining residue (red mud-RM) to produce low carbon cements - Pavia, Sara (My University, 2023)
This paper creates hydraulic binders using waste and a low energy input. Cements are produced with a bauxite refining residue (red mud-RM), blended with limestone and lime, and fused at temperatures from 600 to 1200 °C. The Saudi RM investigated has significant Al and Si but low Ca. Therefore, lime (CaO) and limestone (CaCO 3 ) are used, as a source of calcium, to harvest cementing hydrates.When calcining RM alone, reactive aluminium phases begin to form at c.300 °C. However, at c.900 °C, they turn into crystalline corundum (Al2O3), a more stable and less reactive phase. It is hoped that the Ca provided by the lime/limestone will react with the Al in the RM during fusion, to form reactive silicates and aluminates rather than inert corundum. Both types of fusion produced calcium silicates and aluminates with cementing properties. However, lime fusion required higher temperature. Limestone fusion produces cementing phases at lower temperature than lime fusion, due to the lower decomposition temperature of CaCO 3 when compared to CaO. High temperature is required to break down CaO (melting point = 2572 °C), whereas CaCO 3 decomposes at 600 °C and disappears at 850 °C. Despite the top alkali fusion temperature being much lower than the CaO melting point, the results demonstrate that calcium was released from the lime and entered reactions forming calcium silicates and aluminates. This is probably due to the high alkali content of the RM acting as a flux and lowering the decomposition temperature of the CaO.
PUBLISHED
Keywords: Low- carbon cement; Gehlenite; Bauxite refining residue; Red mud; Alkali fusion; Calcium silicates; Calcium aluminates; Nanoscience & Materials; Smart & Sustainable Planet